The introduction of a base component to porous organic salts and their CO2 storage capability. Issue 15 (28th March 2023) - Ami, Takahiro; Oka, Kouki; Tsuchiya, Keiho; Kosaka, Wataru; Miyasaka, Hitoshi; Tohnai, Norimitsu
Abstract : The introduction of a base component to porous organic salts allows them to have CO2 storage capability. Abstract : Porous organic salts (POSs ) are constructed by charge-assisted hydrogen bonding between amino and sulfonic groups, and can be used to design a variety of porous structures based on molecular design. In particular, triphenylmethylamine (TPMA ) and aromatic sulfonic acids form robust POSs with a rigid diamond structure ( d -POSs ). In this study, by replacing one of the three phenyl rings of TPMA with a pyrimidine ring, we succeeded in constructing a d -POS with high porosity (43.8%) and with a base component (pyrimidine) on the void surface. In addition, the weak basicity of the pyrimidine did not interfere with the formation of d -POSs . This d -POS adsorbed CO2 over the primary air components (N2 and O2 ) and also exhibited CO2 storage capability: It retained CO2 at a relatively low pressure of P e / P 0 = 0.05, and readily desorbed CO2 below P e / P 0 = 0.05.